The Role of Verbal Interaction in Developing Speaking Competence: An Analysis of Fourth-Semester English in classroom - Hasibuan, Derliana; Suhadi, Jumino; Manugeren, M. (Journal of English Language and Education, 2025)
This study investigates the role of verbal interaction in developing speaking competence classroom by analyzing verbal interactions between a lecturer and fourth-semester students at the University of Asahan. Using the Initiation–Response–Feedback (IRF) framework by Sinclair and Coulthard (1975), data were collected through classroom observation and analyzed qualitatively. The findings reveal a predominantly teacher-centered discourse, where lecturers control most exchanges, with limited space for student participation. Although some extended IRF sequences indicated potential for dialogic engagement, overall interaction lacked spontaneity and learner agency. The study recommends adopting more student-centered discourse strategies to foster meaningful participation and promote communicative competence in EFL classrooms